THE ROLE OF KOMIL KHOREZMI IN THE HISTORY OF THE KHIVA KHANATE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes Komil Khorezmi's role in the Khiva Khanate, his contributions to literature, art, and culture, as well as his active participation in the Jadid movement. It provides information about his activities in the politics of the Khiva Khanate.